Evolution of Activity Based Costing (ABC) - A Bibliometric Analysis - Mikki, Sanjana Nee; Sharma, Sunil (Journal of Business Thought, 2022)
Activity Based Costing is an advanced accounting technique that is widely discussed among cost controllers and managers. Through this study, an attempt has been made to identify the recent trends in its evolution and to see further research prospects by doing analysis of the numerous national and international published researches in the related domain. By applying bibliographic analysis technique, output extracted from the Scopus database is analyzed using bibliometrix package in R-software. The results present a structured view of trends in scientific studies on Activity Based Costing in different countries, contribution of pioneer authors and major sectors/industries to which most of the researches catered to. The analysis is carried out using three field plot, most trending topics, a word cloud, arriving at a conceptual structure using co-occurrence map and finally drawing a thematic map. As an application, study may well be a guiding tool for the researchers working in similar area. They can get insights as to what sector to consider for performing further investigations such as case studies or quantitative analysis and to see the effect of applying Activity Based Costing on some particular thematic factors.